Treatment of keloids with intralesional 5-fluorouracil injections compared with triamcinolone in adults - Elias, Lama Georges; Suleman, Hamid; Alkhayer, Abdullah (Journal of medical and pharmaceutical sciences, 2022)
Background: Keloid is a benign proliferation of fibrous tissue that extends beyond the boundaries of the original injury, does not usually regress spontaneously, and tends to recur after surgical excision. Despite several methods of treatment, no standard treatment protocol exists.Objective: Comparison of the efficacy of intralesional triamcinolone acetonide injection versus 5-fluorouracil for the treatment of keloids. In addition to, assessment the side effects of both drugs.Patients and Methods: A prospective comparative study, which included 29 patients (10 males, 19 females) attending the dermatological clinic at Tishreen University Hospital - Lattakia - Syria, their ages ranged from 18 to 53 years, they had 40 keloids distributed into two groups, each group included 20 keloids and treated either by intralesional injection of triamcinolone acetonide or 5-fluorouracil every 3 weeks for up to 6 injections. Results: Both treatments showed comparable efficacy for improving keloid height and vascularity, as well as for patients' personal symptoms such as itching and pain, without significant statistical differences. The treatment with 5-fluorouracil showed more efficacy in improving keloids pliability with a statistically significant difference, while triamcinolone injection was superior to 5-fluorouracil in improving pigmentation, without a statistically significant difference. The most important side effects that were recorded in triamcinolone group were skin atrophy and telangiectasia versus burning sensation and superficial ulceration in 5-fluorouracil group.Conclusion: Intralesional injections of triamcinolone and 5-fluorouracil are effective and safe treatments for keloids. 5-Fluorouracil is recommended as a treatment option for hard keloids. Whereas, treatment with triamcinolone is preferred over 5-fluorouracil for pigmented keloids.
Keywords: Keloid; intralesional injection; triamcinolone acetonide; 5-fluorouracil